Effect of PEG-1500 on Dipyridamole Binding with Erythrocyte Anion Channel - Ramazanov, V. V.; Nardid, Ya. O.; Olejnik, O. A.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2003)
The authors studied the effect of PEG-1500 on ability of dipyridamole to inhibit the H+ ions transport in erythrocytes. It was established that the inhibitor was not bound in anion channel of erythrocytes ghosts in sulfate medium, despite its ability to block the H+ ions entrance into cells. Using of fluoride loaded erythrocytes allowed to assume that dipyridamole’s inhibitory ability in cells placed to sulfate medium is controlled by chloride output flow during Jacobs-Stewart cycle functioning, and that proton transport does not reflect the whole amount of entering sulfate. Dipyridamole blockage of stated fraction of H+ ions transport was considerably withdrawn in PEG-1500 presense due to inhibitor’s redistribution from membrane to cryoprotectant solution.